Transcriptomic inspection revealed a possible pathway regulating the formation of the high-quality brush hair in Chinese Haimen goat (Capra hircus). Issue 1 (10th January 2018) - Ji, Dejun; Yang, Bo; Li, Yongjun; Cai, Miaoying; Zhang, Wei; Cheng, Guohu; Guo, Haiyan
Abstract : The high-quality brush hair, or Type III brush hair, is coarse hair but with a tip and little medulla, which uniquely grows in the cervical carina of Chinese Haimen goat ( Capra hircus ). To unveil the mechanism of the formation of Type III brush hair in Haimen goats, transcriptomic RNAseq technology was used for screening of differentially expressed genes (DEGs) in the skin samples of the Type III and the non-Type III hair goats, and these DEGs were analysed by KEGG pathway analysis. The results showed that a total of 295 DEGs were obtained, mainly from three main functional types: cellular component, molecular function and biological process. These DEGs were mainly enriched in three KEGG pathways, such as protein processing in endoplasmic reticulum, MAPK, and complement and coagulation cascades. These DEGs gave hints to a possible mechanism, under which heat stress possibly initiated the formation. The study provided some useful biological information, which could give a new view about the roles of certain factors in hair growth and give hints on the mechanism of the formation of the Type III brush hair in Chinese Haimen goat.